Forging Digital Pathways to Prosperity: A Mixed-Methods Inquiry into Digital Literacy, Community Entrepreneurship, and Sustainable Development Goal Attainment in Rural Indonesia - Grace Olivia Silalahi; Delia Tamim; Sandro Louise Oliveirra; Abdul Malik; Muhammad Faiz (Indonesian Community Empowerment Journal, 2025)
The proliferation of digital technology presents a monumental opportunity for economic development, yet its benefits remain unevenly distributed, particularly in the rural regions of developing nations like Indonesia. This study investigates the critical role of digital literacy as a catalyst for community entrepreneurship, and its subsequent impact on achieving Sustainable Development Goal 1 (No Poverty) and Goal 8 (Decent Work and Economic Growth). A sequential explanatory mixed-methods design was employed across three diverse rural regencies in Indonesia. The initial quantitative phase involved a multi-stage cluster survey of 525 rural entrepreneurs, with data analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test hypothesized relationships. The subsequent qualitative phase comprised 30 in-depth, semi-structured interviews with entrepreneurs and community leaders, selected purposively from the quantitative sample. Interview data were analyzed using rigorous thematic analysis to explain and enrich the statistical findings. The PLS-SEM analysis revealed that digital literacy has a significant, positive direct effect on both entrepreneurial intention (b=0.451, p<0.001) and entrepreneurial performance (b=0.382, p<0.001). Entrepreneurial performance, in turn, was a strong predictor of progress toward SDG 1 (b=0.523, p<0.001) and SDG 8 (b=0.610, p<0.001). Qualitative findings identified three core mechanisms facilitating these relationships: (1) the use of digital platforms as a gateway to expanded markets, (2) the vital role of informal, peer-to-peer social networks in digital skill acquisition, and (3) the translation of individual entrepreneurial success into community-wide economic benefits through local job creation and value chain development. In conclusion, digital literacy is a foundational capability that directly empowers rural entrepreneurs, driving local economic performance and accelerating progress toward key SDGs. These findings underscore the necessity of moving beyond infrastructure-centric policies to holistic strategies that cultivate digital skills through community-based learning and support the integration of digital tools into local enterprises.